2021
DOI: 10.3389/fpls.2021.733608
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference-Based Forest Protection Products (FPPs) Against Wood-Boring Coleopterans: Hope or Hype?

Abstract: Graphical AbstractThree-tier impact of forest protection products (FPPs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 231 publications
1
26
0
Order By: Relevance
“…According to our knowledge, all the above-mentioned dsRNA delivery methods have not been tested in forest trees for pests and pathogens ever. Studies on dsRNA delivered through artificial diet (feeding), and injection are common among forest insect pests (Joga et al 2021 ). Moreover, none of the forest fungal pathogens have ever been considered, except for some pathogens from the genus Fusarium and Botrytis which are vital pathogens for crops (Koch et al 2016 ; Bennett et al 2020 ).…”
Section: Dsrna Delivery Methods In Woody Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our knowledge, all the above-mentioned dsRNA delivery methods have not been tested in forest trees for pests and pathogens ever. Studies on dsRNA delivered through artificial diet (feeding), and injection are common among forest insect pests (Joga et al 2021 ). Moreover, none of the forest fungal pathogens have ever been considered, except for some pathogens from the genus Fusarium and Botrytis which are vital pathogens for crops (Koch et al 2016 ; Bennett et al 2020 ).…”
Section: Dsrna Delivery Methods In Woody Plantsmentioning
confidence: 99%
“…In the last few years, intensive studies have shown the efficiency of dsRNA against wood-boring forest pests like southern pine beetle, mountain pine beetles, emerald ash borer, Asian longhorn beetles, and Chinese white pine beetle (Joga et al 2021 ). The feeding of many candidate dsRNAs targeting, INHIBITOR OF APOPTOSIS ( IAP ), HEAT SHOCK 70-kDa PROTEIN COGNATE 3 ( HSP ), SHIBIRE ( SHI ), and injecting the β-FRUCTOFURANOSIDASE-ENCODING-2 ( AplaScrB-2 ) genes resulted in more than 80% of mortality to the emerald ash borer (Rodrigues et al 2017a , b , 2018 ).…”
Section: Dsrna Fungi- and Pesticide For Forest Insect Pests And Funga...mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of targets potentially underlying insecticide resistance in L. decemlineata and explored using dsRNA-based approaches are shown in Table 4 . Furthermore, while it is challenging to highlight these studies in the current work, it is relevant to underline that such an approach has seems promising to control a variety of insect pests, including the fall armyworm Spodoptera frugiperda [ 78 ], the whitefly Bemisia tabaci [ 79 ], and the emerald ash borer Agrilus planipennis [ 80 ].…”
Section: Rnai and Insecticide Resistancementioning
confidence: 99%
“…As a pathogen-specific and environmentally friendly technology, SIGS offers excellent potential for plant protection since it does not require transgenic plants, in contrast to Host-Induced Gene Silencing (HIGS) (Wang and Jin, 2017). For SIGS technology to be successful, several essential requirements must be met, including correct selection of target genes, proper design of the dsRNAs (Joga et al, 2021), as well as ensuring that the pathogens can internalize dsRNA molecules (Qiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%